Comparison of obstetrical outcomes in patients undergoing cerclage with or without amniocentesis. (3rd April 2021) - Zaretsky, Michael V.; Rodriguez Riesco, Laura G.; Pan, Zhaoxing; Galan, Henry L.
Abstract: Objective: We sought to compare the obstetrical outcomes in patients who underwent midtrimester cerclage placement with or without prior amniocentesis in a single center cohort. Methods: A retrospective medical record review in a single academic institution was undertaken of all patients who underwent either an exam or ultrasound indicated cerclage. This group was then divided into two groups: amniocentesis or no amniocentesis groups. Detailed maternal data was abstracted from the prenatal and hospital records. Amniocentesis fluid specimens were sent for Gram stain, aerobic and anaerobic bacterial culture, including mycoplasma and ureaplasma, as well as for glucose. Comparisons were performed utilizing Parametric 2-sample t -test for continuous variables and Fisher's exact test was utilized to compare categorical variables. Results: A total of 160 patients who underwent a cerclage were utilized for comparison. Sixty-five patients who had an amniocentesis performed prior to the cerclage were compared with 95 patients who underwent a cerclage without an amniocentesis. None of the amniocentesis results were positive for infection in those that received a cerclage. Patients that had an amniocentesis before cerclage were found to have an earlier gestational age at time of the procedure (20.30 ± 2.29 weeks versus 21.32 ± 1.81 weeks, p < .001), a shorter cervical length on presentation (0.93 ± 0.61 cm versus 1.45 ± 0.66 cm, p < .001), delivered at an earlier gestational age (GA 32.2 [30.3 to 34.2] versus 36.3 [35.2 to 37.3] weeks, p < .001) with shorter time from cerclage placement until delivery (13.9 [0.0 to 24.0] versus 16.3 [0.3 to 23.2] weeks, p = .010). The rates of chorioamnionitis and PPROM were significantly higher in the amniocentesis group (17 versus 2%, p = .0008 and 26 versus 13%, p = .03 respectively). Five patients who underwent an amniocentesis did not receive a cerclage, with one having a positive Gram stain and culture. Conclusion: Amniocentesis use prior to cerclage placement in this single institution cohort was utilized in patients who presented earlier in gestation with shorter cervical length and more cervical dilation. The severity of presentation was the determining factor in the decision to perform an amniocentesis prior to cerclage placement, and, because of this difference in severity, outcomes for the amniocentesis group were predictably worse than those who did not undergo amniocentesis.